Delayed Intracranial Hemorrhage in Patients with Head Trauma and Antithrombotic Therapy - Antoni, Anna (J Clin Med, 2019)
Background: Delayed intracranial hemorrhage can occur up to several weeks after head trauma and was reported more frequently in patients with antithrombotic therapy. Due to the risk of delayed intracranial hemorrhage, some hospitals follow extensive observation and cranial computed tomography (CT) protocols for patients with head trauma, while others discharge asymptomatic patients after negative CT. Methods: We retrospectively analyzed data on patients with head trauma and antithrombotic therapy without pathologies on their initial CT. During the observation period, we followed a protocol of routine repeat CT before discharge for patients using vitamin K antagonists, clopidogrel or direct oral anticoagulants. Results: 793 patients fulfilled the inclusion criteria. Acetylsalicylic acid (ASA) was the most common antithrombotic therapy (46.4%), followed by vitamin K antagonists (VKA) (32.2%) and Clopidogrel (10.8%). We observed 11 delayed hemorrhages (1.2%) in total. The group of 390 patients receiving routine repeat CT showed nine delayed hemorrhages (2.3%). VKA were used in 6 of these 11 patients. One patient needed an urgent decompressive craniectomy while the other patients were discharged after an extended observation period. The patient requiring surgical intervention due to delayed hemorrhage showed neurological deterioration during the observation period. Conclusions: Routine repeat CT scans without neurological deterioration are not necessary if patients are observed in a clinical setting. Patients using ASA as single antithrombotic therapy do not require in-hospital observation after a negative CT scan.